Mapping Vocabulary: A corpus-based comparison of Indonesian fourth-grade students' writing and English language textbooks - Fitria Ningsih (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study compares the vocabulary used by Indonesian fourth-grade students in their free writing with that taught in their English language textbooks to assist language teachers in developing relevant learning materials for young learners. To achieve this, the researchers employed the corpus linguistic method and analyzed the writings of 369 students from 19 public elementary schools in Malang, East Java, Indonesia, along with five selected English textbooks. The University of Adelaide Text Analysis Tool program, AdTAT, was used to analyze the corpus. The program generated word lists consisting of the top 100 words most frequently used by students and the top 100 words used in English textbooks. The findings of the study revealed a 45% match between the top 100 words most frequently used by students and the top 100 words used in English textbooks. This suggests that there is a significant overlap between the vocabulary used in free writing and that taught in textbooks. The implication of this study is that language teachers need to recognize the basic words students acquire before learning new vocabulary to achieve successful learning of the target language. The study suggests that language teachers should incorporate more culturally relevant vocabulary into their teaching materials to better engage and motivate their students. The findings of this study can also assist language curriculum developers in designing more effective and culturally relevant teaching materials for young learners.